2021
DOI: 10.17993/3cemp.2021.100347.109-135
|View full text |Cite
|
Sign up to set email alerts
|

Learning the Chinioti way: exploring the legacy of a family business community leaders’ success based on the entrepreneurial mindset and values of Chinioti Sheikhs

Abstract: The Chinioti Sheikh community ranks among the most successful business communities in Pakistan, yet literature is almost barren of any study that aims to understand the success model of such business communities in the country. The purpose of this paper is twofold: one is to understand the factors that make Chinioti Sheikhs a successful business community in Pakistan and second is to comprehend the role of entrepreneurial mindset and values in the contribution of entrepreneurial success for Chinioti Sheikhs in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
(2 reference statements)
0
2
0
Order By: Relevance
“…The trait of perseverance and determination also affirms a previous study of Chang (2017) who found through personal interviews with successful entrepreneurs that all her participants cherished and advocated these traits. On the other hand, while it is conveniently assumed that an entrepreneur is a risk-taker, we found evidences from the findings that the Chinioti Sheikh entrepreneurs as well as others believe in taking calculated risks, a finding underlined by Chell (2008). Similarly, a common characteristic found in all Chinioti Sheikh entrepreneurs was that they started small; thus, most of their characteristics corresponded with three out of five principles of effectuation (Sarasvathy, 2001), i.e., bird in hand (in terms of starting with their means), affordable loss (in terms of taking calculated risk), and crazy quilt (forming partnerships and taking help from community members).…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…The trait of perseverance and determination also affirms a previous study of Chang (2017) who found through personal interviews with successful entrepreneurs that all her participants cherished and advocated these traits. On the other hand, while it is conveniently assumed that an entrepreneur is a risk-taker, we found evidences from the findings that the Chinioti Sheikh entrepreneurs as well as others believe in taking calculated risks, a finding underlined by Chell (2008). Similarly, a common characteristic found in all Chinioti Sheikh entrepreneurs was that they started small; thus, most of their characteristics corresponded with three out of five principles of effectuation (Sarasvathy, 2001), i.e., bird in hand (in terms of starting with their means), affordable loss (in terms of taking calculated risk), and crazy quilt (forming partnerships and taking help from community members).…”
Section: Discussionmentioning
confidence: 57%
“…Many scholars have tied entrepreneurial success to psychological factors such as personal satisfaction (Chong, 2012), high self-efficacy (Chen et al, 1998), locus of control and need for achievement (Chell, 2008;McClelland, 1965). Some studies have found that entrepreneurs with a persistent mindset tend to be visionary leaders, even if they come from non-family businesses .…”
Section: Entrepreneurial Successmentioning
confidence: 99%